Liquidation and Legal Liability: A Study of the Hajj Hospital of UIN Syarif Hidayatullah Jakarta - Syifa Conita; Arif Saefudin; Imam Subchi; Ulva Fatiya Rosyida; Johan Wahyudhi (PT PUSTAKA CENDEKIA GROUP, 2026)
Purpose: This study aims to analyze the legal implications following the liquidation of PT Rumah Sakit Haji Jakarta and its transformation into Rumah Sakit Haji UIN Syarif Hidayatullah Jakarta. It also seeks to examine whether the liquidation process complies with Law Number 40 of 2007 concerning Limited Liability Companies. Research Methodology: This research applies a normative juridical method using statute and conceptual approaches. The study is based on literature review, utilizing primary legal sources such as Law Number 40 of 2007, Law Number 28 of 2007, and Minister of Religious Affairs Decree Number 459 of 2020. Secondary sources include books, academic journals, prior studies, and official reports, including the 2023 Liquidator Report. Data are analyzed qualitatively through a descriptive-analytical method to interpret legal norms and assess the liquidation process. Results: The findings indicate that the liquidation process was conducted in accordance with applicable laws and did not violate legal provisions. The use of circular shareholder resolutions aligns with Article 91 of Law Number 40 of 2007. The settlement of tax obligations, debts, and assets was completed properly. The transformation into a Public Service Agency (BLU) resulted in significant changes in legal status, governance, and asset ownership. Conclusions: The study concludes that the liquidation process is legally valid and consistent with corporate law. The involvement of UIN Syarif Hidayatullah Jakarta remains lawful as long as the liquidation is executed by an authorized liquidator. The legal status shifts from private corporate law to public administrative law. Limitations: This study is limited to normative legal analysis without empirical data such as interviews or field observations. Contributions: This study contributes to the development of corporate and administrative law, especially in cases of non-conventional liquidation involving public institutions. It benefits academics, legal practitioners, and policymakers